Molecular dynamics simulations reveal how characteristics of surface and permeant affect permeation events at the surface of soft matter. Issue 5 (13th April 2017) - Oroskar, Priyanka; Jameson, Cynthia J.; Murad, Sohail
Abstract: Molecular dynamics simulations are particularly useful in providing details that permit understanding of phenomena occurring at surfaces, phenomena characterised by surface-sensitive experimental methods yielding average properties. The methods and examples that we consider here reveal how the characteristics of the surface and the permeant affect permeation events at the surface of soft matter, in particular, lipid bilayers. We choose permeation of lipid membranes as our example of the ability of molecular dynamics simulations to provide molecular-level mechanisms that are otherwise not available via other means. Molecular permeation through lipid membranes is a fundamental biological process that is important for small molecules such as therapeutics as well as nanoparticles that have become important modes of drug delivery. We describe methods applicable to such large systems and use examples where the permeants are uncharged particles: small molecules (Xe, O2, CO2 ), bare gold nanocrystals, gold-core nanoparticles with hydrophobic ligands (alkane thiols of various lengths) and gold-core nanoparticles with hydrophilic ligands (methyl-terminated polyethylene glycol of various lengths). In each example, we have previously validated our findings by comparisons with experimental data, using such information as is available from X-ray diffraction, electron paramagnetic resonance, nuclear magnetic resonance, atomic force microscopy, various imaging methods, diffusion measurements, dynamic light scattering. In addition to spherical core nanoparticles, we also examine the characteristic permeation mechanisms of gold nanorods with polyethylene glycol ligands, where the aspect ratio different from 1 makes the permeation event dependent on the angle of the rod axis relative to the membrane surface. This review examines the phenomena associated with the interaction of various permeants with the lipid bilayer that serves as our model membrane. We consider adsorption at the interface, the permeant within the top lipid leaflet, in the middle of the membrane within the lipid tail region, within the bottom lipid leaflet and finally exiting the membrane on the way to recovery, for various permeants: gas molecules, bare gold nanocrystal, gold nanoparticles with alkane thiol ligands, PEGylated gold nanoparticles and PEGylated gold nanorods. We observe formation of a water pore, occasional transport of ions, lipid flip-flops, lipid displacement from the membrane, and rotational behaviour of PEGylated nanorods during the permeation process. These events differ depending on the chemical nature (hydrophobic or hydrophilic) of the ligands, their length, the coverage density on the gold surface and the aspect ratio of the gold core. Direct comparisons across the board are possible by using identical interaction models (MARTINI coarse grain), molecular dynamics methods, simulation set-ups and analyses of MD results, thereby permitting generalisations to be made about mechanisms for the various events and how they are affected by these factors.